Higher mortality rates amongst emergency patients admitted to hospital at weekends reflect a lower probability of admission - Meacock, Rachel (J Health Serv Res Policy, 2016)
OBJECTIVE: Patients admitted as emergencies to hospitals at the weekend have higher death rates than patients admitted on weekdays. This may be because the restricted service availability at weekends leads to selection of patients with greater average severity of illness. We examined volumes and rates of hospital admissions and deaths across the week for patients presenting to emergency services through two routes: (a) hospital Accident and Emergency departments, which are open throughout the week; and (b) services in the community, for which availability is more restricted at weekends. METHOD: Retrospective observational study of all 140 non-specialist acute hospital Trusts in England analyzing 12,670,788 Accident and Emergency attendances and 4,656,586 emergency admissions (940,859 direct admissions from primary care and 3,715,727 admissions through Accident and Emergency) between April 2013 and February 2014.Emergency attendances and admissions to hospital and deaths in any hospital within 30 days of attendance or admission were compared for weekdays and weekends. RESULTS: Similar numbers of patients attended Accident and Emergency on weekends and weekdays. There were similar numbers of deaths amongst patients attending Accident and Emergency on weekend days compared with weekdays (378.0 vs. 388.3). Attending Accident and Emergency at the weekend was not associated with a significantly higher probability of death (risk-adjusted OR: 1.010). Proportionately fewer patients who attended Accident and Emergency at weekend were admitted to hospital (27.5% vs. 30.0%) and it is only amongst the subset of patients attending Accident and Emergency who were selected for admission to hospital that the probability of dying was significantly higher at the weekend (risk-adjusted OR: 1.054). The average volume of direct admissions from services in the community was 61% lower on weekend days compared to weekdays (1317 vs. 3404). There were fewer deaths following direct admission on weekend days than weekdays (35.9 vs. 80.8). The mortality rate was significantly higher at weekends amongst direct admissions (risk-adjusted OR: 1.212) due to the proportionately greater reduction in admissions relative to deaths. CONCLUSIONS: There are fewer deaths following hospital admission at weekends. Higher mortality rates at weekends are found only amongst the subset of patients who are admitted. The reduced availability of primary care services and the higher Accident and Emergency admission threshold at weekends mean fewer and sicker patients are admitted at weekends than during the week. Extending services in hospitals and in the community at weekends may increase the number of emergency admissions and therefore lower mortality, but may not reduce the absolute number of deaths.